Receptiveness of Spanish and flamenco professional dancers in their training and development - de las Heras Fernández, Rosa; García Coll, M. Virginia; Espada-Mateos, María (International Journal of Instruction, 2020)
The concept of coaching is an important object of study in the development of sports coaches, and the relationship between athletes and coaches may define the professional life of the former. In the area of dance, the figure of the coach is represented by teachers, choreographers and directors; however, there are few studies that analyse the different forms of coaching and receptiveness in the training of dance professionals. Therefore, the aim of this study was to ascertain the receptiveness of professional Spanish dance and flamenco dancers to the coaching abilities of their respective teachers, directors or choreographers. The sample consisted of 143 dancers, 96 women (67.1%) and 47 men (32.9%) aged between 18 and 51 (30.52±7.86), who were students in their last year of a Higher Degree, or professionals from different companies specialising in Spanish dance and flamenco. The most relevant results show that there were significant statistical differences in receptiveness to coaching according to age, with the older dancers showing less receptiveness. Similarly, there were significant statistical differences according to the company in which the dancers carried out their professional work.
Keywords: keywords; professional dance; flamenco dance; leadership; professional companies; dancer; dance training; Scopus; Emerging